Shoulder muscle activity in sport climbing in naturally chosen and corrected shoulder positions - Baláš, J.; Duchacová, A.; Giles, D.; Kotaliková, K.; Pánek, D.; Draper, N. (The Open Sports Sciences Journal, 2017)
Objective: The aim of the study was to determine electromyographic activity of the scapula stabilizing muscles in naturally chosen and corrected shoulder positions in typical static climbing postures. Methods: Six male participants undertook surface electromyography measurement in four climbing postures for two different shoulder positions. The activity of the lower, middle and upper trapezius, serratus anterior, pectoralis major, and sternocleidomastoid was recorded. Electromyographic activity was expressed as the percentage of maximal voluntary contraction (MVC) for each muscle. Results: Climbing postures induced higher activation of middle and lower trapezius in corrected shoulder positions (35.3 ± 11.8 and 61.7 ± 15.4% MVC respectively) than in naturally chosen shoulder positions (18.4 ± 8.9 and 30.1 ± 13.8% MVC respectively). The highest activity of the middle and lower trapezius was found in postures with the arm in external rotation and 90° abduction and in an overhanging posture. Low activation was stated for the other muscles in both shoulder conditions. Conclusion: Results showed that climbers naturally elevate the shoulder during typical static postures. Corrected shoulder positions induce higher activation of the scapula stabilizing muscles than naturally chosen shoulder positions.